The fate of antibiotic resistance genes during co-composting of swine manure with cauliflower and corn straw. (March 2020) - Li, Houyu; Cheng, Weimin; Li, Bihan; Xu, Yan; Zheng, Xiangqun
Highlights: The effect on ARGs removal under different composting conditions was explored. Bacterial community had significant difference in three treatment during composting. The shift of bacterial community had significant influence on ARGs variation. Compost environmental factors (TOC, TN, NH3-N, pH) were correlated with ARGs level. Abstract: Composting is not completely effective in reducing antibiotic resistance genes (ARGs) in animal manure. This work studied the effects of different treatment conditions on the fate of ARGs in composting swine manure with cauliflower and corn straw as bulking agents. The results showed that the addition of microbial agents or the ratio of corn stalks to cauliflower (1:12) could significantly decrease the absolute abundances of most ARGs (an average of 480 times) compared with the control treatment. Principal component analysis indicated that bacterial communities were significantly correlated with ARG abundance, suggesting that microbial communities have an impact on ARG variation during co-composting. Redundancy and Network analysis confirmed the changing patterns of individual ARGs ( qnr S, bla AmpC, bla TEM-1 ) were influenced by the selectivity of host bacteria ( Pseudomonas, Klebsiella, and Halocella ) and environmental variables (TN, NH3 -N, TOC, and pH). These findings helped to optimize composting conditions, thereby reducing the risk of ARGs spread.